2019
DOI: 10.2147/cmar.s221225
|View full text |Cite
|
Sign up to set email alerts
|

<p>Thoracic Radiotherapy Benefits Elderly Extensive-Stage Small Cell Lung Cancer Patients with Distant Metastasis</p>

Abstract: Purpose: Thoracic radiotherapy (TRT) is the recommended therapeutic regimen for extensive-stage small cell lung cancer (ES-SCLC). Little is known about TRT benefits in elderly populations. The aim of this study was to evaluate TRT effects on the prognosis of elderly patients with ES-SCLC. Patients and methods: This retrospective analysis reviewed the records of patients over 65 years of age with metastatic ES-SCLC treated between 2010 and 2016. Enrolled patients received standard chemotherapy regimens (etoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
3
1
Order By: Relevance
“…In our study, the median PFS2 was 2.400 months. Our results were similar to Qi et al's study (20); however, our study differs from other studies as it included only patients with extensive disease and consisted of two stages, both of which were prospective studies. Further exploration with the inclusion of the survival time of patients with ES-SCLC is needed.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the median PFS2 was 2.400 months. Our results were similar to Qi et al's study (20); however, our study differs from other studies as it included only patients with extensive disease and consisted of two stages, both of which were prospective studies. Further exploration with the inclusion of the survival time of patients with ES-SCLC is needed.…”
Section: Discussionsupporting
confidence: 90%
“…The pooled results showed that the addition of TRT still improved the prognosis of patients over 65 years of age. In addition, previous studies have demonstrated that ES-SCLC patients with a single metastatic site were more suitable for radiotherapy as they had lower disease burden (16,24,25). However, our study did not observe the benefit of TRT for OS in patients with only one organ metastasis.…”
Section: Discussioncontrasting
confidence: 89%
“…A total of 4,754 studies were excluded by screening titles and abstracts. After reading the full text of the remaining 237 studies, 12 studies were eventually included in the meta-analysis: 3 RCTs and 9 retrospective studies (5)(6)(8)(9)(10)(11)(16)(17)(18)(19)(20)(21). The selection process of the study is shown in Figure 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations